Sperm Membrane: Molecular Implications and Strategies for Cryopreservation in Productive Species - Macarena Castro; Karla Leal; Felipe Pezo; María José Contreras (Animals)
Sperm cryopreservation is a fundamental reproductive biotechnology, enabling the long-term storage of genetic material and supporting assisted reproduction programs. Despite its widespread application, the process is associated with significant limitations due to the cryo-induced cellular damage that occurs during freezing and thawing. These injuries primarily affect the plasma membrane, nuclear DNA, and motility, thereby compromising the fertilizing potential of spermatozoa. Furthermore, interspecies variability in terms of cryo-sensitivity poses a major challenge to the development of standardized cryopreservation protocols. Recent advances have focused on mitigating cryodamage through the use of various strategies. The inclusion of antioxidants in cryopreservation media has proven effective in reducing oxidative stress, thereby enhancing cellular protection. Similarly, the addition of lipid-based supplements contributes to membrane stabilization, improving post-thaw sperm viability and functionality. Moreover, the application of omics technologies, such as transcriptomics and proteomics, has facilitated a deeper understanding of molecular damage and protective responses, paving the way for the development of tailored, species-specific protocols. These integrated approaches optimize cryopreservation conditions, maximizing post-thaw survival and the fertilizing capacity of sperm. Enhancing cryopreservation techniques not only improves the outcomes of assisted reproductive technologies, but also plays a crucial role in the conservation of genetically valuable livestock species. In conclusion, the integration of biotechnological and molecular tools holds significant promise for overcoming the current limitations and advancing the efficacy of sperm cryopreservation.